Influence of pre-treatment of black mass from spent electric vehicle batteries on lithium recovery - Usman Saleem; Hammad Farooq; Erik Prasetyo; Christian Rosenkilde; Sulalit Bandyopadhyay (Chemical Engineering Journal Advances)
This study focused on maximizing early-stage lithium (Li) recovery from different thermally pre-treated industrial black masses (BMs) of spent batteries using water leaching. A design of experiments was performed to optimize the leaching conditions. At 80 °C, 30 mins, and pH 10, Li leaching efficiency of 68 % and 53 % at 20 and 150 g/L solid/liquid ratios, respectively, were obtained. The pH of the BMs varied with pre-treatment and should be maintained during leaching for Li selectivity, reducing copper and aluminum from 385 to 320 to ∼5 mg/L. Li precipitation was performed from leachates prepared at solid/liquid ratios (g/L) of 20 (total evaporation) and 150 (evaporative concentration). The former yielded different Li phases, while the latter precipitated a single phase of technical grade. The developed process can recycle different industrial BMs using optimized process conditions, with the produced leachates possibly serving as alternative feed to post-processing operations of Li production from brines.